Keratoacanthoma of the Lip. Issue 38 (September 2015) - Dillenburg, Caroline Siviero; Martins, Manoela Domingues; Meurer, Luise; Castilho, Rogerio Moraes; Squarize, Cristiane Helena; Tobouti., Priscila
<x xml:space="preserve">Abstract</x> Abstract The PI3K-PTEN-mTOR is one of the most important pathways involved in cancer development and progression; however, its role in keratoacanthoma (KA) is poorly understood. In this study, we investigated the activation of key proteins in the PI3K-mTOR pathway in lip KA. We analyzed the activation of the PI3K-PTEN-mTOR pathway using human tumor samples stained for well-established protein markers in this pathway, including pS6 and pAKT phosphoproteins. We assessed proliferation using Ki-67 and performed additional morphological and immunohistochemical analysis using anti-PTEN and anti-p16 antibodies. We found that the majority of KA labeled to pS6 and not pAKT. PTEN expression was inversely correlated with Ki-67 expression. In addition to PTEN expression, KA cells were positive for p16Ink4 senescence marker. PI3K-PTEN-mTOR pathway is activated in lip KA, leading to downstream activation of mTORC1, but not mTORC2. This pathway plays an important role in KA progression by promoting proliferation and activation of oncogenic-induced senescence.